Deagrarianization and Livelihood Dislocation of Peasant Community in Rural Java - Pujiriyani, Dwi Wulan; Soetarto, Endriatmo; Santosa, Dwi Andreas; Agusta, Ivanovich (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2018)
ABSTRACTThis study aim to analyze the deagrarianization phenomena occurring in peasant communities in rural Java. The research was done by explanative case study approach. The emic perspective is used to perform close reading through participation observation. Data is obtained through the collection and analysis of individual experiences (life history). Data analysis was done descriptively. The result shows that character as an agrarian village still survives. The villages still have peasants and active agriculture activity. Agriculture still in production. Nevertheless, the characteristic of agrarian community as the base of agrarian village, certainly experiencing a decay. Agrarian community are not peasants who cultivate their agricultural land, but they are ‘quasy peasants’ who hire other people to do it. The real deagrarianizaton threats come from within peasant community itself. Agriculture was stopped in the second generation. The third generation from community more attached to various non-agriculture activities that grows exclusively.Keywords: quasi peasant, agriculture, deagrarianization, communityABSTRAKPenelitian ini menganalisis fenomena deagrarianisasi yang terjadi pada komunitas petani di pedesaan Jawa. Penelitian dilakukan dengan pendekatan studi kasus eksplanatif. Perspektif emik digunakan untuk melakukan pembacaan jarak dekat (close reading) melalui partisipasi observasi. Data diperoleh melalui pengumpulan dan penganalisaan pengalaman individu (life history). Analisis data dilakukan secara deskriptif. Hasil penelitian menunjukkan bahwa karakter sebagai desa agraris masih tetap bertahan. Desa masih memiliki petani dan masih menunjukkan aktivitas pertanian yang dilakukan secara aktif. Produksi pertanian masih berjalan. Meskipun demikian karakter komunitas agraris sebagai penopang desa agraris mengalami peluruhan secara pasti. Komunitas agraris bukanlah petani yang mengerjakan lahannya sendiri, tetapi mereka adalah ‘petani semu’ yang mempekerjakan orang lain untuk mengolah sawah. Ancaman deagrarianisasi yang nyata bukan berasal dari luar komunitas, melainkan hadir dari dalam komunitas petani sendiri. Pertanian secara aktif berhenti pada generasi kedua. Generasi ketiga dari komunitas petani lebih lekat dengan berbagai aktivitas non pertanian yang tumbuh semakin eksklusif.Kata kunci: petani semu, pertanian, deagrarianisasi, komunitas